2021
DOI: 10.1021/acsomega.1c05422
|View full text |Cite|
|
Sign up to set email alerts
|

Wetting Mechanism and Experimental Study of Synergistic Wetting of Bituminous Coal with SDS and APG1214

Abstract: To solve the problem of poor dust wettability during coal mine dust treatment, sodium dodecyl sulfate (SDS) and alkyl glycoside (APG1214) were selected for compounding. An efficient, environmentally friendly, economical wetting agent was prepared. First, through molecular dynamics simulation studies, it was determined that the tail group C of SDS and APG1214 was adsorbed on the surface of bituminous coal, and the head groups S and O were adsorbed on the surface of water. The simulation result is found to be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Based on this, the Gemini surfactant Surfynol 465 with low foaming property and high hydrophilicity was used as the main raw material . To make the moist dust particles continue to absorb water in the air and prevent the occurrence of dust re-entrainment, the alkyl glycoside APG1214 with good surface activity and compound performance and sucrose with strong hygroscopicity were selected as auxiliary materials. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, the Gemini surfactant Surfynol 465 with low foaming property and high hydrophilicity was used as the main raw material . To make the moist dust particles continue to absorb water in the air and prevent the occurrence of dust re-entrainment, the alkyl glycoside APG1214 with good surface activity and compound performance and sucrose with strong hygroscopicity were selected as auxiliary materials. , …”
Section: Methodsmentioning
confidence: 99%
“…14 To make the moist dust particles continue to absorb water in the air and prevent the occurrence of dust reentrainment, the alkyl glycoside APG1214 with good surface activity and compound performance and sucrose with strong hygroscopicity were selected as auxiliary materials. 15,16 3.2. Dust Samples.…”
Section: Dust Suppression Componentsmentioning
confidence: 99%
“…The tail chains of the two surfactants were intertwined, the oxygen atoms in the −SO 3 − of the headgroup formed hydrogen bonds with the hydrogen atoms of water, and the normal angle between the tail chain of SDBS and the oil−water interface was small. Sun et al 10 found that the interaction between SDS and APG1214 and coal surface was greater than that between water and coal. When the ratio was 1:3 and the total concentration was 0.7%, the combined surfactant had the best wettability on the coal surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Experimental studies aimed at improving the wettability of coal seams and gas extraction efficiency concentrated on water injection and gas injection displacement. Research on water injection focused on the use of surfactants. Surfactants are the main wetting agents in improving wettability, and surface tension is a key parameter for their effectiveness. Jiang et al found that OP-10 surfactant solutions had the best effect on improving coal wettability based on surface tension and contact angle measurements of different wetting agents. , Several studies have explored the effect of wetting agents in different proportions or combined with other materials to improve the wettability of coal seams. , For instance, Zou et al added water-based SiO 2 nanofluids to the wetting agent solution and proposed a water injection method for coal seam improvement. , Molecular simulation software has been employed by some scholars to investigate the mechanism of surfactant effect on enhancing coal seam wettability. ,, In addition, the COMSOL simulation software was used to develop a coupled damage model during water injection to increase gas extraction rates. , Studies on gas injection displacement for improving gas extraction rates can be categorized into two types: using gases with strong adsorption capacity or gases that can break the dynamic balance of coal seam gas. CO 2 -enhanced coalbed methane (CO 2 -ECBM) technology is essential to ensure energy security and achieve the “dual carbon” goal. This technology is crucial for achieving the low-carbon, clean, and efficient utilization of coal-based fossil energy.…”
Section: Introductionmentioning
confidence: 99%